2022
DOI: 10.1038/s41467-022-32043-3
|View full text |Cite
|
Sign up to set email alerts
|

A long-acting formulation of rifabutin is effective for prevention and treatment of Mycobacterium tuberculosis

Abstract: Tuberculosis (TB) is a communicable disease caused by Mycobacterium tuberculosis (Mtb) and is a major cause of morbidity and mortality. Successful treatment requires strict adherence to drug regimens for prolonged periods of time. Long-acting (LA) delivery systems have the potential to improve adherence. Here, we show the development of LA injectable drug formulations of the anti-TB drug rifabutin made of biodegradable polymers and biocompatible solvents that solidifies after subcutaneous injection. Addition o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 56 publications
2
10
0
Order By: Relevance
“…Our exposure-activity data for rifabutin align with that reported by Kim et al, who found that a long-acting biodegradable in situ forming implant of rifabutin that maintained plasma concentrations above 0.064 μg/mL, a reported ECOFF concentration (17,18) selected as a target for up to 18 weeks post-injection, exhibited potent anti-TB activity in mouse models (13). The formulation developed by Kim et al is therefore especially promising given that our data suggest that far lower target concentrations of rifabutin may be sufficient for efficacy in TPT regimens.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our exposure-activity data for rifabutin align with that reported by Kim et al, who found that a long-acting biodegradable in situ forming implant of rifabutin that maintained plasma concentrations above 0.064 μg/mL, a reported ECOFF concentration (17,18) selected as a target for up to 18 weeks post-injection, exhibited potent anti-TB activity in mouse models (13). The formulation developed by Kim et al is therefore especially promising given that our data suggest that far lower target concentrations of rifabutin may be sufficient for efficacy in TPT regimens.…”
Section: Discussionsupporting
confidence: 88%
“…The physiochemical properties of another rifamycin antibiotic, rifabutin, appear even more favorable than rifapentine for LAI formulation (5,8). Although only currently indicated for prevention and treatment of nontuberculous mycobacterial disease (9,10), rifabutin has demonstrated potent anti-TB activity in preclinical models, including preclinical models of TPT (11)(12)(13)(14)(15), and has been used off-label for prevention and treatment of TB (reviewed in (16)). The suitability of rifabutin as a long-acting formulation is highlighted in a recent publication by Kim et al describing the development of long-acting biodegradable in situ forming implants of rifabutin (13).…”
Section: Introductionmentioning
confidence: 99%
“…A long acting injectable of PLGA was developed to deliver rifabutin, which solidifies after subcutaneous injection. In vivo results show high plasma drug concentration and quick clearance of M.tb from lungs . In this direction, Table shows the clinical and preclinical status of various TB vaccines.…”
Section: Specific Diseasesmentioning
confidence: 97%
“…In vivo results show high plasma drug concentration and quick clearance of M.tb from lungs. 58 In this direction, Table 3 shows the clinical and preclinical status of various TB vaccines.…”
Section: Worldwide Statisticsmentioning
confidence: 99%
“…Paliperidone palmitate was used as a representative approved and marketed LAI formulation for which PK and drug depot histopathology data in rat models were published [10,11]. In this study, we also included assessment in a mouse model, as mouse models are often used in pre-clinical treatment models of infectious diseases, including mouse models of tuberculosis used to evaluate developmental LAI formulations of anti-tuberculosis drugs [12][13][14].…”
Section: Introductionmentioning
confidence: 99%